ANALISIS KESULITAN BELAJAR MENUL ANALISIS KESULITAN BELAJAR MENULIS TEKS OBSERVASI DI KELAS X SMA EKA PRASETYA MEDAN - Siswati, Eka Dewi; Sitorus, Friska Ria; Perangin-angin, Esra (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
This study aims to describe the forms of difficulties experienced by tenth-grade students of Eka Prasetya Senior High School Medan in writing observation texts, to identify and analyze the factors contributing to these difficulties, and to examine the strategies employed by teachers to address them. Using a qualitative phenomenological approach, the research explores students’ perceptions of the challenges they face in writing observation texts, with detailed data collection through direct interaction with the principal, Indonesian language teachers, and students. The findings reveal that students’ difficulties in writing observation texts are primarily related to linguistic aspects and text structure. The contributing factors include the lack of engaging learning models and overly monotonous, teacher-dominated instruction. To overcome these difficulties, teachers applied several strategies, such as providing contextual text examples and step-by-step guidance to understand structure and language, facilitating direct observation with supervision and written feedback, and implementing scaffolding techniques through object selection, outlining, drafting, and intensive revision support. Teachers also utilized visual media and technology to concretize object understanding, encouraged collaborative group discussions to foster idea exchange and strengthen comprehension of text structure, and provided personalized and constructive feedback to improve students’ writing. Furthermore, teachers built students’ motivation and self-confidence by appreciating their writing process and gradual progress.